PENGEMBANGAN BAHAN AJAR KAJIAN APRESIASI PROSA FIKSI BERBASIS KEARIFAN LOKAL TERINTEGRASI MOBILE LEARNING - Haslinda Haslinda (JURNAL KONFIKS, 2017)
The purpose of this research is to create study materials of fictional prose based on local wisdom of Makassar integrated mobile learning that is feasible or valid, readability, practical and effective for the students of Indonesian Language and Literature Education Study Program at Muhammadiyah University of Makassar.This research type is research and development or Research and Development (R D) by using model of ADDIE (Analyze, Design, Develop, Implement, Evaluation).  Data collection techniques include test techniques, questionnaires, observation, interviews, and documentation. Data analysis techniques used descriptive qualitative analysis techniques and descriptive statistics. In this research, it is found that the appropriate or valid teaching material is evaluated from the teaching material element (4.32) or with the category very feasible, the presentation element (4.07) or with the decent category, the element of kegrafikan (4,33) or with the category very feasible, linguistic element (4.19) or by a viable category, and the last element of media or technology (4.19) with a decent category. The average of one-to-one subject assessment subjects totaling six students is (3.75) or with the appropriate category, the average of the feasibility of the main field trial subjects (4.38) with very feasible category, and the average assessment of the feasibility of the field trial operational is 4.38 with very decent category. Teaching materials have a good level of legibility with a mean percentage of (81.45%) greater than the independence independence standard (60%). The result of the assessment of teaching materials implementation proves that the average of evaluation of 1st class implementation learning program is (4.25) or with very decent category, implementation class 2 is (4.40) or with very decent category, and implementation class 3 is 4.60 ) or in a very decent category. Furthermore, the use of teaching materials in learning shows excellent results. The teaching materials are implemented maximally where the average implementation class 1 is (4.20) or in very practical category, the implementation class 2 is (4.60) or in the very practical category, and the implementation class 3 is (4.50) or with category very practical.Teaching materials are worth using because they are effective towards improving student learning outcomes. The test results prove that there is an increase in students' learning mastery. The result of the initial skill test is only (22%) of the students who is declared thoroughly while the final skill test result is (76%).